2014
DOI: 10.5114/fn.2014.43788
|View full text |Cite
|
Sign up to set email alerts
|

Original article Involvement of D 2 /D 2 dopamine antagonists upon open-arms exploratory behaviours induced by intra-nucleus accumbens shell administration of N-methyl-D-aspartate

Abstract: A b s t r a c t Glutamatergic system stimulation in some parts of the brain may affect anxiety-related behaviours

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
1
2
0
Order By: Relevance
“…We postulate that novelty-induced rearing may represent risk-taking or impulsivity. The KOR-stimulated increase in avoidance behavior is consistent with prior observations of its aversive effects in the caudal NAc shell [8] and has previously been associated with reduced dopamine release and activity in the NAc shell [39,40]. Finally, while locomotor activity is commonly thought to involve the NAc core rather than shell, a reduction of dopamine with application of 7-OH-DPAT in the NAc shell has been shown to decrease locomotor activity [41].…”
Section: Discussionsupporting
confidence: 85%
“…We postulate that novelty-induced rearing may represent risk-taking or impulsivity. The KOR-stimulated increase in avoidance behavior is consistent with prior observations of its aversive effects in the caudal NAc shell [8] and has previously been associated with reduced dopamine release and activity in the NAc shell [39,40]. Finally, while locomotor activity is commonly thought to involve the NAc core rather than shell, a reduction of dopamine with application of 7-OH-DPAT in the NAc shell has been shown to decrease locomotor activity [41].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, we hypothesize that the novelty-induced rearing may represent increased risk-taking or impulsivity. Increased anxiety-like behavior, as measured in an elevated plus maze, has been associated with reduced dopamine release and activity in the NAc shell (Avena et al, 2008;Razavi et al, 2014), and the ability of the KOR to induce anxiety-like or avoidance behavior in the present study is in line with prior observations of its aversive effects in the caudal NAc shell (Castro & Berridge, 2014). Finally, while the effect of dopamine on locomotor activity is commonly thought to involve the NAc core, a reduction of dopamine with application of 7-OH-DPAT in the NAc shell has also been found to decrease locomotor activity (Clements & Greenshaw, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As the amygdala is known to mediate memories with emotional content (Herry et al, 2010 ; Lüthi and Lüscher, 2014 ) and to project extensively to the AcbShm (Heimer et al, 1997 ), it is plausible that amygdala-AcbShm projections modulate the effect of anxiety on AcbShm MSN activation. Regions medial of the nucleus accumbens i.e., the major island of Calleja and intermediate part of the lateral septum as well as the medial septum/diagonal band complex have also been shown to be affected by rewarding/reinforcing effects of drugs of abuse (Mahler and Aston-Jones, 2012 ; Prast et al, 2014 ) or by anxiety (Menard and Dallas, 1996 ; Degroot and Treit, 2003 ; Razavi et al, 2014 ). For instance, it has been shown that neurons in the lateral septum were specifically activated during cue-induced cocaine seeking (Mahler and Aston-Jones, 2012 ) or that the cocaine CPP reacquisition-induced EGR1 expression was increased in the medial septum/diagonal band complex and also in the major islands of Calleja and the intermediate part of the lateral septum (Prast et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%